Ecofriendly management of weeds in rice - Sindhu P V (Department of Agronomy, College of Horticulture, 2008)
Competition from weeds and consequent yield reduction is a major problem in rice cultivation, which warrants proper weed management strategies. The present study was undertaken to develop and refine stale seed bed techniques and subsequent cultural practices for semi-dry and wet-seeded rice and to find out the optimum plant spacing, which can give maximum weed control efficiency coupled with better grain yield. Survey and documentation of prevailing weed control practices followed by rice farmers was another objective of the study.